Aplikasi Pemilihan Model Rambut Pria Berdasarkan Bentuk Wajah Berbasis Android - Stefanus Kevin Joses; Henry Novianus Palit (Jurnal Infra, 2017)
Currently, when someone went to barber, they usually can’t decide which hair models that they want. When the hairstyle that the hairstylist choose didn’t match, it can make people have bad appearances. Because good hairstyle its one of the important part to make good appearances.To decide hairstyle that looks good on someone, by the opinion of [7] face shape is the most important thing for choosing hairstyle that looks good on someone, if the hairstyle didn’t match with their face shape, they will have a bad appearances. So by that factor the writer want to develop an android application for choosing a man’s hairstyle based on his face shape.The accuracy of this application training for determine a man’s face shape development is 90.952% and the result from the survey to 5 hairstylist, they say that this application is really help people choose what kind of hairstyle that suit them.